Slime production a virulence marker in Pseudomonas aeruginosa strains isolated from clinical and environmental specimens: A comparative study of two methods - Prasad S; Ballal Mamatha; Shivananda P (Wolters Kluwer Medknow Publications, 2009)
Detection of slime in Pseudomonas aeruginosa can be useful in understanding the virulence of this organism. Here, comparative studies of two phenotypic methods using the tube method and the spectrophotometric method for slime production from 100 clinically and 21 environmentally significant isolates of P. aeruginosa were performed. A total of 68 isolates were positive by either of the tests whereas only 34 were positive by both the tests. The tube method detected slime significantly in more number of isolates than the spectrophotometric method. The tube test was found to be superior to the spectrophotometric method in ease of performance, interpretation and sensitivity. Among the clinical isolates, systemic isolates produce less slime compared to wound, respiratory and urinary isolates. Isolates from the hospital environment produced more slime indicating that this virulence marker helps the organism to survive for longer periods and cause nosocomial infections.